2017
DOI: 10.2147/copd.s129325
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health aspects among persons living with chronic obstructive pulmonary disease

Abstract: PurposeTo describe a cohort of chronic obstructive pulmonary disease (COPD) patients and perform a within-group comparison regarding self-management activation, social provision, and health status.Patients and methodsA cross-sectional survey including 116 persons.ResultsThe sample comprised 65 men and 38 women, mean age 69 years. Fourteen percent reported very high impact of COPD on their health; 19% had received pulmonary rehabilitation offers, 39% had been offered self-management education, and 64% had acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
3
10
0
1
Order By: Relevance
“…During the past decade, various studies investigated the relationships between demographic and clinical characteristics and self-management among persons with chronic diseases, including COPD. 10 14 The findings have indicated that age, 10 , 11 being female, 12 educational achievement, 10 , 12 social support, 10 and physical health 12 are positively associated with self-management, whereas no associations are found with self-management and lung function, dyspnea, body mass index, and hospitalization. 13 In addition, those with a very high symptom burden have been found to score significantly lower on self-management.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the past decade, various studies investigated the relationships between demographic and clinical characteristics and self-management among persons with chronic diseases, including COPD. 10 14 The findings have indicated that age, 10 , 11 being female, 12 educational achievement, 10 , 12 social support, 10 and physical health 12 are positively associated with self-management, whereas no associations are found with self-management and lung function, dyspnea, body mass index, and hospitalization. 13 In addition, those with a very high symptom burden have been found to score significantly lower on self-management.…”
Section: Introductionmentioning
confidence: 99%
“… 13 In addition, those with a very high symptom burden have been found to score significantly lower on self-management. 14 These studies, though, have employed self-management as an umbrella term and did not specifically explore the different domains of self-management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicated that relevant factors mainly include psychological factors (such as not wanting to face the occurrence or aggravation of the disease), no experience in coping with the disease, and lack of external support, but external support is also proposed as a contributing factor [50] [51] [52]. Mullerova et al [53] concluded that high expectations of disease, poor health, and low satisfaction with health care workers are also barriers.…”
Section: Factors Influencing the Empowerment Of Patients With Copdmentioning
confidence: 99%
“…Medforskarane var sterkt involverte i utviklinga av det siste skjemaet, og prosjektgruppa testa alle skjemaa ved å fylle dei ut sjølve. Forskarane gjorde statistiske analysar, og alle var med på å velje ut funn til publisering og utforming av publikasjon (21). Forskarane laga førsteutkast til tekst på norsk, og dette vart presentert og diskutert på prosjektmøte der brukarane kom med kommentarar og innspel.…”
Section: Metodeunclassified